Gene expression of Ntann12 in Nicotiana tabacum to Pb treatment - Abdul Halim, Nurul Izzah; Phang, Ing Chia (2013)

(untitled)
Plants are sessile organisms that are unable to move away from adverse environmental conditions. In order to survive or adapt their growth to environmental stresses, plants undergo physiological, biochemical and molecular changes. Lead (Pb), on the other hand, is a widespread heavy metal pollutant that is commonly found in the environment. It is highly persistent and causes toxicity to plants, animals, and human. To advance our understanding in Pb tolerance in plants and subsequently develop phytoremediation technology, there is a need to identify genes associated with Pb stress.